Find My Way to You: A Comparative Study of Antennal Sensilla and Olfactory Genes in Slug Moth With Different Diet Ranges (Lepidoptera: Limacodidae) - Li, Jing; Yang, Yi-ming; Wang, Ying; Yang, Cai-qing; Wang, Gui-fang; Wu, Chun-sheng; Zhang, Ai-bing (Frontiers in Ecology and Evolution, 2022)
Insects and plants that provide them with foods have coexisted for several hundred million years, leading to various defense approaches and insect-feeding strategies. The host plant provides insects with food sources, shelter materials, and oviposition sites for phytophagous insects. However, they need to find the most suitable host plants in complicated plant communities. The antenna is the main sensory organ of insects, housing different types of sensilla dedicated to detecting chemical cues, motion, humidity, and temperature. Phytophagous insects with different diets may possess various adaptations in their olfactory system and host-plant searching behavior. We selected three species of slug moth (Narosoideus flavidorsalis, Chalcoscelides castaneipars, and Setora postornata) with different diet breadth to detect the structural diversity of antennal sensilla using the scanning electron microscope. A total of 9 types of sensilla were identified in these three species, in which two types of sensilla (sensilla uniporous peg and sensilla furcatea) were the first found and reported in Limacodidae. By comparing the number of sensilla types, there was a trend of gradually decreasing the number of sensory types with the gradual expansion of feeding habitats. To better understand the vital roles of olfactory proteins in localizing host plants, we investigated the chemosensory proteins in the antennal transcriptomes of N. flavidorsalis and S. postornata. However, there was no significant correlation between the number of olfactory genes and the increase of antennal sensilla types . By combining antennal morphology, transcriptomes analysis and prediction of suitable areas, we better understood the olfactory systems with different feeding preferences, which will provide new prospects for plant-insect interactions and population control methods.